The knowledge and attitude of the Turkish community pharmacists toward pharmacovigilance in the Kadikoy district of Istanbul - (:unkn) unknown (SPRINGER, 2008)
Objective We investigated the knowledge and attitudes of community pharmacists towards pharmacovigilance and adverse drug reactions (ADRs) in Kadikoy district of Istanbul (Turkey). Setting The community pharmacies in Kadikoy. Kadikoy is one of the biggest districts of Istanbul and has the largest number of pharmacies. Kadikoy district was divided into two regions, the central and the peripheral. Method Between December 2005 and June 2006 we conducted a survey about the knowledge and attitude of community pharmacists (n = 219) using a face-to-face questionnaire. The questionnaire consisted of questions about the sociodemographic characteristics of the pharmacists, their knowledge of pharmacovigilance and their attitudes towards ADR reporting. Main outcomes measured The knowledge of pharmacovigilance practice, ADR reporting compliance rates, reasons for not reporting ADR and perceptions of the Turkish community pharmacists on pharmacovigilance practice were evaluated. Results Although all 411 pharmacies in the Kadikoy district were visited, only 53% of the community pharmacists (n = 219) consented to participate in the study. Of those that did respond, only 17.2% of the pharmacists had any knowledge about 'pharmacovigilance'. Sixty-five percent of the pharmacists stated that patients reported an ADR to them during the previous 12 months, and 21% of pharmacists reported to the concerned organizations. Our survey showed that only 7% actually reported an ADR to the national pharmacovigilance center. On the other hand, 89% of the pharmacists believed that the role of the pharmacist in ADR reporting was essential. Conclusion The results show that Turkish community pharmacists have poor knowledge about pharmacovigilance. There is an urgent need for educational programs to train them about pharmacovigilance and ADR reporting.
Keywords: adverse drug reaction reporting; attitude; community pharmacist; community pharmacy; knowledge; pharmacovigilance; Turkey; ADVERSE DRUG-REACTIONS; NORWAY